Risk and rate advancement periods of total hip replacement due to primary osteoarthritis in relation to cumulative physical workload - Rubak, Tine Steen; Svendsen, Susanne Wulff; Søballe, Kjeld; Frost, Poul (Scandinavian Journal of Work, Environment & Health, 2013)
' ' OBJECTIVES ': 'This study aims to (i) evaluate relative risks, excess fraction of cases, and rate advancement periods for total hip replacement (THR) due to primary osteoarthritis in relation to lifelong cumulative physical workload and (2) describe temporal trends in the proportion employed in the most highly exposed industries from 1986–2006. ' ' METHODS ': 'In a cohort study of the Danish working population, we assessed cumulative physical workload by combining year-by-year register information on employment industry with an industry exposure matrix that provided point scores (0–2) of physical workload. Cumulative physical workload was expressed as point-years corresponding to the pack-year concept of smoking. We retrieved register information on first-time THR during 1996–2006 and used a logistic regression technique to fit discrete time hazards models adjusting for age and other factors. We calculated excess fraction of cases and rate advancement periods. ' ' RESULTS ': 'Total numbers of point-years ranged from 0–86. For men, an exposure–response relation was observed reaching an odds ratio of 1.33 [95% confidence interval (95% CI) 1.17–1.53] for the highest exposure category (35–86 point-years) compared to 0 point-years. The excess fraction of cases was 18%, and THR took place up to 3.4 years earlier with increasing exposure. For women, no exposure–response relation was found. ' ' CONCLUSIONS ': 'At the population level, cumulative physical workload increased the risk of THR among men, with surgery being performed slightly earlier in life. The proportion employed in the most highly exposed industries remained constant.
Keywords: cohort study; cumulative physical workload; epidemiology; excess fraction; exposure assessment; industry exposure matrix; osteoarthritis; physical workload; primary osteoarthritis; register study; risk and rate advancement period; risk estimation; total hip replacement